Free-Radical-Mediated Glycan Isomer Differentiation - Murtada, Rayan (Anal Chem, 2020)
The inherent structural complexity and diversity of glycans pose a major analytical challenge to their structural analysis. Radical chemistry has gained considerable momentum in the field of mass spectrometric biomolecule analysis, including proteomics, glycomics, and lipidomics. Herein, seven isomeric disaccharides and two isomeric tetrasaccharides with subtle structural differences are distinguished rapidly and accurately via one-step radical-induced dissociation. The free-radical-activated glycan-sequencing reagent (FRAGS) selectively conjugates to the unique reducing terminus of glycans in which a localized nascent free radical is generated upon collisional activation and simultaneously induces glycan fragmentation. Higher-energy collisional dissociation (HCD) and collision-induced dissociation (CID) are employed to provide complementary structural information for the identification and discrimination of glycan isomers by providing different fragmentation pathways to generate informative, structurally significant product ions. Furthermore, multiple-stage tandem mass spectrometry (MS(3) CID) provides supplementary and valuable structural information through the generation of characteristic parent-structure-dependent fragment ions.